Evaluation of Human Resources Pillars in Industry Readiness Index to Transform towards Industry 4.0 - Sayekti, Andita; Suhariadi, Fendy; Herachwati, Nuri (RSF Conference Series: Business, Management and Social Sciences, 2023)
Developed countries have implemented Industry 4.0 in the process and manufacturing industry sectors. Industry 4.0 transformation will positively impact the industry and the country. Indonesia introduced a guide for the industry in transforming to Industry 4.0 in its action for Making Indonesia 4.0. The Indonesia Industry 4.0 Readiness Index (INDI 4.0) is presented to assist the industry in carrying out transformations, with the pillar of human resources as the highest parameter. It is necessary to conduct an early evaluation of the industry to introduce INDI 4.0. This research aims to evaluate the level of industry readiness in transforming to Industry 4.0. The method in this study used a survey of Small and Medium Industries (SMI=IKM) in Bogor City. Three SMIs were selected for interviews according to INDI 4.0 guidelines and Toolbox Industrie 4.0. The evaluation results using the INDI 4.0 guidelines show that SMI A has a higher level of readiness, followed by SMI C and B. In line with the results of the INDI 4.0 assessment, Toolbox Industrie 4.0 also has the same results. SMI A has a higher level of readiness, followed by SMI C and B. In Toolbox Industrie 4.0, there is no element of assessment for human resources due to cultural differences between Germany and Indonesia, which still require special attention for human resources.